Development of an image-based analysis method to determine the physical composition of a mixed waste material - Wagland, Stuart T.; Veltre, F.; Longhurst, Philip J. (Elsevier, 2012)
An experimental study was undertaken to assess the suitability of an image-based approach for determining the physical composition of mixed organic wastes. Samples arriving at different waste sorting facilities, each visited twice during the study, were physically sorted to examine the composition these materials. During these surveys the waste was processed in order to obtain digital images covering 30 m 2 , representing approximately 250-500 kg of mixed waste. The images were processed using ERDAS  Imagine software in order to assess the area covered by each component within the waste material. The composition determined from the image analysis was compared with the results from the physical hand sorting. The image analysis results indicated a strong correlation between the physical results (mean r = 0.91) however it was evident that components such as film plastics and paper were over-estimated by the image analysis approach. This short communication provides initial results, demonstrating the potential  of an image-based method, and discusses further research requirements and future applications of this technique.